Association Between Hyperacute Stage Blood Pressure Variability and Outcome in Patients With Spontaneous Intracerebral Hemorrhage. Issue 2 (February 2018) - Chung, Pil-Wook; Kim, Joon-Tae; Sanossian, Nerses; Starkmann, Sidney; Hamilton, Scott; Gornbein, Jeffrey; Conwit, Robin; Eckstein, Marc; Pratt, Frank; Stratton, Sam; Liebeskind, David S.; Saver, Jeffrey L.
Abstract : Background and Purpose—: Increased blood pressure (BP) variability, in addition to high BP, may contribute to adverse outcome in intracerebral hemorrhage. However, degree and association with outcome of BP variability (BPV) in the hyperacute period, 15 minutes to 5 hours after onset, have not been delineated. Methods—: Among consecutive patients with intracerebral hemorrhage enrolled in the FAST-MAG trial (Field Administration of Stroke Therapy-Magnesium), BPs were recorded by paramedics in the field and during the first 24 hours of hospital course. BP was analyzed in the hyperacute period, from 0 to 4–6 hours, and in the acute period, from 0 to 24–26 hours after onset. BPV was analyzed by SD, coefficient of variation, and successive variation. Results—: Among 386 patients with intracerebral hemorrhage, first systolic BP at median 23 minutes (interquartile range, 14–38.5) after onset was median 176 mm Hg, second systolic BP on emergency department arrival at 57 minutes (interquartile range, 45–75) after onset was 178 mm Hg, and systolic BP 24 hours after arrival was 138 mm Hg. Unfavorable outcome at 3 months (modified Rankin Scale, 3–6) occurred in 270 (69.9%). Neither mean nor maximum systolic BP was associated with outcome in multivariable analysis. However, all 3 parameters of BPV, in both the hyperacute and the acute stages, were associated with poor outcome. In the hyperacute phase, BPV was associated with poor outcome with adjusted odds ratios of 3.73 for the highest quintile of SD, 4.78 for the highest quintile of coefficient of variation, and 3.39 for the highest quintile of successive variation. Conclusions—: BPV during the hyperacute first minutes and hours after onset in patients with intracerebral hemorrhage was independently associated with poor functional outcome. Stabilization of BPV during this vulnerable period, in the pre-hospital and early emergency department course, is a potential therapeutic target for future clinical trials. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00059332. Abstract : Supplemental Digital Content is available in the text.